الحقوق المالية للزوج عند وفاة الزوجة في العدة: دراسة فقهية مقارنة - الجبوري، فهد شلاش خلف (جامعة الموصل - كلية العلوم الإسلامية, 2022)
الحمد لله رب العالمين والصلاة والسلام على المبعوث رحمة للعلمين سيدنا محمد وعلى آله وصحبه أجمعين. أما بعد: إن موضوع العدة للزوجة من المواضيع المهمة التي شرعها الله تعالى، ولعل من أهم أسبابها هو الحفاظ على الأنساب، وكذلك معرفة الحقوق بين الزوجين لذا الواجب على الزوجين هو ضبط وقت بداية العدة ونهايتها لما له من أثر في ضبط ما مر ذكره من أسبابها، وقد تطرقت في هذا البحث لموضوع الحقوق المالية للزوج عندما تتوفي زوجته في العدة؛ لأن كثيرا من الباحثين تطرق لدراسة الحقوق المالية للزوجة أثناء وفاة الزوج، لذلك سوف أسلط الضوء في هذا البحث على تعريف العدة، وأنواعها، ودليل مشروعية كل نوع منها، ثم بيان حقوق الزوج المالية عند طلاق زوجته طلاقا رجعيا في حال الصحة، وميراثه منها عندما ترتد عن الإسلام في حال صحتها، وكذلك حقوق الزوج المالية في حال خلع الزوجة لزوجها في حال مرض الموت، وارتكاب الزوجة أثناء مرض موتها فعلا يتسبب في فسخ النكاح، وبيان أقوال الفقهاء، والقول الراجح، وأسأل الله التوفيق والسداد. Praise be to God, Lord of the Worlds, and prayers and peace be upon the one who was sent as a mercy to the worlds, our master Muhammad and all his family and companions. Then: The subject of the waiting period for the wife is one of the important topics legislated by God Almighty, and perhaps one of its most important reasons is the preservation of lineages, as well as knowledge of the rights between spouses, so the duty of the spouses is to control the time of the beginning and end of the waiting period because of its impact in controlling the aforementioned causes, and I have touched upon In this research on the subject of the husband's financial rights when his wife dies in the waiting period; Because many researchers dealt with the study of the financial rights of the wife during the death of the husband, so I will highlight in this research the definition of the kit, its types, and the evidence of the legality of each type, then the statement of the husband's financial rights when divorcing his wife in a revocable divorce in the case of health, and his inheritance from her when she relapses About Islam in the event of her health, as well as the husband's financial rights in the event of the wife's divorce from her husband in the event of a death illness, and the wife's commission during her death illness actually causes the annulment of the marriage, and the statement of the scholars' sayings, and the most correct saying, and I ask God for success and payment.
Keywords: الحقوق المالية -- العدة الزوجية -- الفقه الإسلامي -- الشريعة الإسلامية